Pharmaceutical Biotechnology Products in the Form of Hand Washing Soap Kombucha Bunga Telang (Clitoria ternatea L) as Antibacterial for Salmonella thypi and Listeria monocytogenes - Devita Anugrah Anggraini; Firman Rezaldi; Anggita Sofianti; Irmawati Mathar; Yuliana Kolo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The growth of Salmonella thypi and Listeria monocytogenes bacteria can be inhibited by butterfly pea flower kombucha. This is because telang flower kombucha has pharmacological activity so it can be developed in the pharmaceutical field. This research needs to be carried out to make hand washing soap made from an active solution of telang kombucha diffusing solution so that it can stop the growth of Salmonella thypi and Listeria monocytogenes bacteria. The research method uses laboratory experiments. The data obtained were then analyzed using One Way Analysis of Variance and post hoc. The results of the study showed that the formulation and preparation of hand washing soap with a concentration of 40% active ingredient in a solution of butterfly pea flower was able to stop the growth of both bacteria with a P value <0.05. In conclusion, these two bacteria can be inhibited with hand washing soap containing 40% of a decoction of butterfly pea flower kombucha.